Further validation of the association between MAPT haplotype-tagging polymorphisms and Alzheimer’s disease: neuropsychological tests, cerebrospinal fluid biomarkers, and APOE genotype - Babić Leko, Mirjana; Španić Popovački, Ena; Willumsen, Nanet; Nikolac Perković, Matea; Pleić, Nikolina; Zubčić, Klara; Langer Horvat, Lea; Vogrinc, Željka; Boban, Marina; Borovečki, Fran; Zemunik, Tatijana; de Silva, Rohan; et al. (Frontiers in Molecular Neuroscience, 2024)
IntroductionGenetic studies have shown that variants in the microtubule-associated protein tau (MAPT) gene, which encodes tau protein, can increase the risk for Alzheimer’s disease (AD). Additionally, two haplotypes of the MAPT gene (H1 and H2) are associated with various neurodegenerative disorders, including AD. This study aimed to test the association of MAPT haplotypes (H1 and H2) and MAPT haplotype-tagging polymorphisms (rs1467967, rs242557, rs3785883, rs2471738, del–In9, rs7521) with AD.MethodsThe study included 964 individuals: 113 with AD, 53 with mild cognitive impairment (MCI), 54 with other dementias, and 744 healthy controls.ResultsThe results showed that individuals carrying the A allele in the MAPT rs1467967 polymorphism, the GG genotype in the MAPT rs7521 polymorphism, and the G allele in the MAPT rs242557 polymorphism had worse performance on various neuropsychological tests. Carriers of the C allele in MAPT rs2471738 polymorphism and CC homozygotes also showed worse performance on neuropsychological tests and pathological levels of several cerebrospinal fluid (CSF) biomarkers. However, T allele carriers in the MAPT rs2471738 polymorphism were more represented among patients with dementia and apolipoprotein E (APOE) ɛ4 carriers. Carriers of the H2 MAPT haplotype had worse performance on various neuropsychological tests, consistent with our previous study, which associated the H2 MAPT haplotype with pathological levels of CSF AD biomarkers. Regarding the MAPT rs3785883 polymorphism, further research is needed since both the AA and GG genotypes were associated with pathological levels of CSF and plasma AD biomarkers.DiscussionIn conclusion, further genetic studies are needed to elucidate the role of MAPT haplotypes and MAPT haplotype-tagging polymorphisms in the development of AD.